2008
DOI: 10.1038/ejhg.2008.102
|View full text |Cite
|
Sign up to set email alerts
|

Replication of the Wellcome Trust genome-wide association study of essential hypertension: the Family Blood Pressure Program

Abstract: Essential hypertension is a principal cardiovascular risk factor whose origin remains unknown. Classical genetic studies have shown that blood pressure is at least partially heritable, opening a window to understanding the pathophysiology of essential hypertension in the human using modern genetic tools. The Wellcome Trust Case Control Consortium has recently published the results of screening the genomes of 2000 essential hypertension cases and 3000 controls using 500 000 genome-wide single nucleotide polymor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 14 publications
3
51
0
2
Order By: Relevance
“…The Family Blood Pressure Program could not replicate any hypertensive associations for the six top-ranking SNPs revealed by Wellcome Trust Case Control Consortium. 31 No doubt, complexity of blood pressure regulation is related to a number of phenomena. They include the possible multiple pleiotropic variants of low penetrance, genetic epistasis, ethnic diversity, phenotypic heterogeneity and uncontrolled environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The Family Blood Pressure Program could not replicate any hypertensive associations for the six top-ranking SNPs revealed by Wellcome Trust Case Control Consortium. 31 No doubt, complexity of blood pressure regulation is related to a number of phenomena. They include the possible multiple pleiotropic variants of low penetrance, genetic epistasis, ethnic diversity, phenotypic heterogeneity and uncontrolled environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…3 K Recently several genome-wide association studies have been performed on blood pressure and hypertension to identify the genetic factors. [4][5][6][7][8][9][10][11] What this study adds K This study provides an opportunity to identify causative non-synonymous genetic variations in a hypertension genome-wide association study. K On the basis of previous reports, newly identified genes ADC, PLD2 and BDNF seem to be relevant to hypertension, suggesting the reliability of this approach.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Although the FBPP did not reproduce the results of the WTCCC study, one (rs1937506) of the six SNPs was found to be associated with hypertension in Hispanic Americans and European Americans. 5 To explore the genetic basis of prevalent, lifestyle-related complex diseases in Korea, we launched the KARE (Korean Association REsource) project in 2007. Participants (n¼10 038) aged 40-69 years in the Ansung (n¼5018) and Ansan (n¼5020) community-based cohorts were genotyped using the Affymetrix SNP Array 5.0.…”
Section: Introductionmentioning
confidence: 99%
“…3 To address the genetic risk factors for hypertension, many association studies have been conducted on the basis of casecontrol comparisons, as well as population-based analyses of both candidate genes and the entire genome. [4][5][6][7][8][9] The first genome-wide association study was carried out by the Wellcome Trust Case Control Consortium (WTCCC), which enrolled 2000 hypertensive patients and 3000 normotensive controls. 4 Although no single SNP (single nucleotide polymorphism) achieved genome-wide significance (Po5Â10 -7 ), six variants were found to be highly associated with hypertension (Po10 À5 ).…”
Section: Introductionmentioning
confidence: 99%